Happy Workers, Better Business: Job Satisfaction, Quality of Work Life, Employee Performance - Kusuma Agdhi Rahwana; Eeng Ahman; Suryana Suryana; Yana Setiawan (AIBPM Publisher, 2025)
This study aims to examine the effect of Quality of Work Life on employee performance in the embroidery industry in Tasikmalaya, with job satisfaction as a mediating variable. The research employs a quantitative explanatory approach using primary data collected from 304 employees through an online questionnaire, analyzed using Structural Equation Modeling with SmartPLS 4.0. The results show that Quality of Work Life does not have a significant direct effect on employee performance (? = 0.037; P-value = 0.530). However, Quality of Work Life has a positive and significant effect on job satisfaction (? = 0.493; P-value = 0.000), and job satisfaction significantly influences employee performance (? = 0.254; P-value = 0.037). Furthermore, job satisfaction mediates the relationship between Quality of Work Life and employee performance (? = 0.125; P-value = 0.042), indicating a full mediation effect. This study provides novel evidence that Quality of Work Life influences performance indirectly through psychological mechanisms rather than directly, particularly in labor-intensive industries. The findings highlight the importance of enhancing job satisfaction as a strategic approach to improving employee performance.